Subsistence strategies and the origin of early Neolithic community in the lower Don River valley (Rakushechny Yar site, early/middle 6th millennium cal BC): First results. (10th March 2020) - Dolbunova, Ekaterina V.; Tsybryi, Viktor V.; Mazurkevich, Andrey N.; Tsybryi, Andrey V.; Szmańda, Jacek; Kittel, Piotr; Zabilska-Kunek, Mirosława; Sablin, Mikhail V.; Gorodetskaya, Susanna P.; Hamon, Caroline; Meadows, John
Abstract: The multilayer settlement Rakushechny Yar situated in the lower Don River (Rostov region, Russia) is one of the oldest early Neolithic sites in this region, dated to the 7th and 6th millennia BC. Recent investigations have shown a particular importance of this site in the study of the spread of the Near Eastern "Neolithic package" and the neolithisation of Eastern Europe. Long-term study has provided unique evidence of lives of ancient communities. New 14 C dates contribute to refining the chronology of the recently excavated to dating the development of cultural traditions more precisely. The excellent preservation state of organic materials led to uncovering a rich assemblage of faunal and fish remains, household constructions, hunting and fishing tools, as well as pottery. The subsistence strategies and the life cycle of these communities were reconstructed through multiple proxies, which describe a particular system of resource management determined by specific economic, environmental and cultural conditions. Rich fish remains, shell middens, site location, specific toolkit with restricted categories, and incomplete context of tool production testify all that it was a specialized site for aquatic resource procurement. Faunal remains indicated the use of resources from other ecological niches as well. Finds of bones of domesticated animals in the same Early Neolithic layers may suggest even a more complicated organization of this ancient community and may indicate the northern limit of the Neolithic package distribution.